2018
DOI: 10.1002/fuce.201700143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co‐Ni Ratio in Graphene Based Bimetallic Electro‐catalyst for Methanol Oxidation

Abstract: In this paper the electro‐catalytic oxidation of methanol is studied on the non‐noble catalysts Ni–Co/graphene. The bimetallic electro‐catalyst was prepared with different Co–Ni ratios by using simple solution synthesis method. The synthesized materials were characterized by X‐ray diffraction (XRD) and scanning electron microscopy (SEM) for their structure and morphological changes. The electro‐catalytic activity of Ni–Co/graphene for methanol oxidation was investigated by cyclic voltammetry (CV) on glass carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Over potential is calculated by using the formula (E-E o ) [58]. Among all the composites (i.e., 1-5 wt% and 8 wt% rGO-NiO/CuO MOF and NiO/CuO MOF), 5 wt% rGO-NiO/CuO MOF shows the lowest over potential value; this suggests that the inclusion of rGO may not only increase the catalyst surface area but it may also make the accessibility of reactant toward electrode easier and consequently, it apprehends more ions and exhibits higher activity for the oxidation of methanol [59,60]. However, the over potential value of 8 wt% rGO-NiO/CuO MOF is low from 1 wt% and NiO/CuO MOF and high from 2, 3, 4, 5 wt%; these results illustrate a good correspondence with the CV results as they show low current density because of agglomeration of rGO sheets that results in lower surface area and may hinder the ions from reaching the electrode surface.…”
Section: Resultsmentioning
confidence: 99%
“…Over potential is calculated by using the formula (E-E o ) [58]. Among all the composites (i.e., 1-5 wt% and 8 wt% rGO-NiO/CuO MOF and NiO/CuO MOF), 5 wt% rGO-NiO/CuO MOF shows the lowest over potential value; this suggests that the inclusion of rGO may not only increase the catalyst surface area but it may also make the accessibility of reactant toward electrode easier and consequently, it apprehends more ions and exhibits higher activity for the oxidation of methanol [59,60]. However, the over potential value of 8 wt% rGO-NiO/CuO MOF is low from 1 wt% and NiO/CuO MOF and high from 2, 3, 4, 5 wt%; these results illustrate a good correspondence with the CV results as they show low current density because of agglomeration of rGO sheets that results in lower surface area and may hinder the ions from reaching the electrode surface.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of studies have shown that transition metals (Ni Co Fe Cu) and their oxides (NiO, Co 3 O 4 and CuO) exhibit good electrocatalytic activity and become a substitute for precious metals. Sarwar et al [ 13 ] prepared a Co-Ni/graphene composite catalyst and tested it in a methanol fuel cell. It is found that increasing the concentration of nickel in the composite catalyst can significantly promote the oxidation reaction of methanol.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene coated Co-Ni 4 with its maximum current density of 22.5 mA cm À 2 and minimum resistance and tafel slope prove to be a good catalyst for oxidation process in alkaline medium. [40] Co 3 O 4 /N-rGO synthesized by Liang et al exhibit excellent activity for oxygen reduction (ORR) and oxygen evolution reaction (OER). In OER current density of 10 mA cm À 2 is delivered at 1.54 V (vs RHE) while in ORR half wave potential was found to be 0.83 V at 1600 rpm as a result of four electron transfer process measured by RDE [41] .…”
Section: Introductionmentioning
confidence: 99%